Granulometria por difração a laser e sua relação com a faciologia das rochas argilosas da Formação Corumbataí-SP - Christofoletti, S. R.; Moreno, M. M.T. [UNESP] (FapUNIFESP (SciELO), 2017)
This study examined the relationship between the particle size distribution by laser diffraction and facies analysis of clay deposits of the Corumbataí Formation used as raw material for the ceramic tile industry. 16 geological sections of active and inactive mines in the east-central region of São Paulo state were studied. According to the results obtained by laser diffraction of milled samples, the greatest concentration of particles was distributed in the range of 10≤φ≤100 mm with an average of 58.3%, classified as coarse siltstone to very fine sand. The second largest concentration was in the range 1≤φ≤10 mm with an average of 31.5%, classified as coarse siltstone. Followed with values of 4.9% for the range of 100≤φ≤1000 mm rated medium fine siltstone, and 4.1% for the range of 0.01≤φ≤1 mm essentially composed of clay minerals. The identified lithofacies were: massive, laminated, intercalated silty, intercalated sandy, and altered. By grouping the samples in lithofacies, the best distribution of the particles for packaging purposes occurred in the massive lithofacies and the worst distribution in intercalated sandy lithofacies with high presence of particles in the range 100≤φ≤1000 mm with average of 15.4%. According to the results of facies analysis coupled with the high concentration of particles in the ranges of 1≤φ≤10 and 10≤φ≤100 mm, it is inferred that the raw materials studied, when applied to the ceramic process, can result in products with high water absorption values due to the predominant presence of sandy lithofacies and the largest particle size selection, which decrease the particle packaging during pressing hindering the sintering process. The facies analyses combined with laser particle size analysis are important tools in predicting the ceramic behavior.
Grain size distribution by diffraction laser and its relationship with the faciology clay rocks of the Corumbataí Formation-SP
Keywords: Ceramic; Corumbataí Formation; Facies analysis; Grain size; Laser diffraction